(untitled) (Samriddhi Journal of Development Studies, 2022)
This study surveys university students in Kathmandu valley to examine the impact of peer influence, parental influence and financial literacy on their saving behavior. The study was conducted among undergraduate and post graduate students in Kathmandu valley. Data obtained were analyzed using regression analysis and descriptive analysis such as percentage and frequency. It was discovered that saving behavior of students is significantly influenced by their peers, parents and financial literacy. The analysis further showed that income, age, gender and education level (undergrad and post grad) had no impact on their saving behavior. Hence, financial literacy, peer influence and parental influence were found to be most influential predictors of saving behaviors of university students in Kathmandu.